2020
DOI: 10.1007/s00417-020-04932-0
|View full text |Cite
|
Sign up to set email alerts
|

Macular edema secondary to retinal vein occlusion in a real-life setting: a multicenter, nationwide, 3-year follow-up study

Abstract: Purpose To evaluate the presence of macular edema secondary to retinal vein occlusion (RVO)-both central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO)-3 years after diagnosis in patients who underwent intravitreal therapy and to identify potential prognostic factors and biomarkers of persistent macular edema. Methods National multicenter, observational, exploratory, retrospective cohort study of 104 consecutive patients with macular edema secondary to RVO diagnosed from January 2014 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…However, increasing evidence suggests an association between superior functional (increased BCVA) and anatomical (reduced CMT) outcomes and beginning steroid treatment earlier [52,61,[63][64][65]. Although steroids are associated with increased IOP and cataract formation [80], this is not an inevitable outcome for all of the patients treated with steroids, as studies reported these side effects in less than half of patients. In addition, side effects could be caused not only by steroids but also by the preservatives used in their preparation [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, increasing evidence suggests an association between superior functional (increased BCVA) and anatomical (reduced CMT) outcomes and beginning steroid treatment earlier [52,61,[63][64][65]. Although steroids are associated with increased IOP and cataract formation [80], this is not an inevitable outcome for all of the patients treated with steroids, as studies reported these side effects in less than half of patients. In addition, side effects could be caused not only by steroids but also by the preservatives used in their preparation [44].…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that this may have been because conbercept only inhibits downstream VEGF inflammatory mediators and does not affect the upstream inflammatory mediators of VEGFs, such as PGE1, PGE2, and PGF2a [75]. Costa et al reported that intravitreal anti-VEGF injections are prioritized over other treatment methods, including macular grid photocoagulation [80]. Compared with steroid injections, anti-VEGFs are superior because they have fewer side effects; as with their use in DME, steroids are associated with a higher incidence of increased IOP and cataract formation [80].…”
Section: Macular Edema Secondary To Retinal Vein Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the visual prognosis of CRVO is still not any better than that for branch retinal vein occlusion (BRVO). [13][14][15] It is known that the baseline best-corrected visual acuity (BCVA) is the strongest predictor for the nal BCVA in eyes with CRVO. [16][17][18][19][20] However, a PubMed search did not extract any study examining the background factors of the patients that were signi cantly associated with poorer BCVAs at the initial visit to the hospital.…”
Section: Main Textmentioning
confidence: 99%
“…At present, several different types of treatments have been used for eyes with a CRVO, including laser photocoagulation [ 8 ], intravitreal injection of corticosteroids including triamcinolone acetonide [ 9 ], intravitreal implantation of dexamethasone [ 10 ], and intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents [ 11 , 12 ]. However, the visual prognosis of CRVO is still not good [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%